PENGELOLAAN AGROFORESTRI TRADISIONAL “DUSUNG” SEBAGAI SOLUSI PENINGKATAN EKONOMI MASYARAKAT DI NEGERI WAAI KECAMATAN SALAHUTU - Sahureka, Mersiana; Wattimena, Cornelia M. A.; Latupapua, Lesly (Universitas Pattimura, 2023)
Agroforestry is a form of land use carried out by the community, namely a combination pattern of agricultural crops, plantations and forestry. Currently, agroforestry management practices have been widely implemented and provide many benefits both economically, ecologically and culturally. Waai Country, which is located in the Salahutu sub-district, Central Maluku Regency, generally has residents who earn their living as farmers and fishermen. People in Waai country still apply traditional agroforestry management patterns, namely dusung, which is a form of local wisdom in Maluku that is still maintained from generation to generation. The partners' priority problems are decreasing land productivity which directly affects land yields, lack of public interest, especially generations, in farming, and not enriching the types of forestry plants in the hamlets. The solution offered to partners is the realization and stages of activities carrying out extension activities, training activities and planting 100 MPTs (Multi Purpose Tree Species) plant saplings in the village, which will provide various results for the sustainability of the ecosystem and community economy.